1994
DOI: 10.1143/jjap.33.4115
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lithium-Drifted Silicon Detectors Using an Automatic Lithium-Ion Drift Apparatus

Abstract: Using a computer-controlled drift apparatus, we have developed lithium-ion drift techniques to produce large-size silicon detectors with a high success rate. Based on the improved techniques, we have made detectors with a 115×25×2 mm3 sensitive volume. The variation of the detector sensitivity has been shown to be homogeneous over the measurement area using 1150 nm infrared light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There is also one report indicating that it is empirically preferable for Li drift [22]. Resistivity of ∼1000 Ω · cm corresponds to an acceptor concentration of N A ≈ 10 13 atoms/cm 3 [19], which is an order of magnitude lower density than that used in some of previous studies of large-area Si(Li) detectors [20][21][22][23]. Substrate with a lower p-type acceptor concentration requires fewer Li ions for compensation, thus reducing the temperature and time required in the diffusion process.…”
Section: Procurement Of P-type Si Crystalmentioning
confidence: 98%
See 4 more Smart Citations
“…There is also one report indicating that it is empirically preferable for Li drift [22]. Resistivity of ∼1000 Ω · cm corresponds to an acceptor concentration of N A ≈ 10 13 atoms/cm 3 [19], which is an order of magnitude lower density than that used in some of previous studies of large-area Si(Li) detectors [20][21][22][23]. Substrate with a lower p-type acceptor concentration requires fewer Li ions for compensation, thus reducing the temperature and time required in the diffusion process.…”
Section: Procurement Of P-type Si Crystalmentioning
confidence: 98%
“…Several studies have reported that uniformly drifting Li ions into a thick, large-area, p-type Si wafer is difficult mainly due to defects and contaminants, such as oxygen and carbon, in the Si crystal [20][21][22][23][32][33][34]. These behave as traps for Li ions and hence decrease Li ion mobility in the crystal, making it hard to uniformly drift.…”
Section: Procurement Of P-type Si Crystalmentioning
confidence: 99%
See 3 more Smart Citations